Active Cycle of Breathing Technique (ACBT) and Effective Coughing on Respiratory Rate Changes in COPD Patients - Sawitri, Atri Mega; Yuniarti, Enny Virda; Pratiwi, Rizky Meuthia (Poltekkes Kemenkes Semarang, 2024)
Background: COPD is a chronic obstructive disease that causes breathing resistance, resulting in an increase in respiratory frequency. To reduce shortness of breath in COPD patients, independent nursing interventions can be carried out, one of which is providing a combination of Active Cycle of Breathing Technique (ACBT) techniques. In addition to loosening and relieving the respiratory tract.Purpose: this study aimed to evaluate the effectiveness of Active Cycle of Breathing Technique (ACBT) and effective coughing in reducing respiratory rate among patients with Chronic Obstructive Pulmonary Disease (COPD).Methods: using a pre-experimental design with a one-group pretest-posttest approach, 30 COPD patients from Dr. Wahidin Sudirohusodo Regional General Hospital were recruited via purposive sampling technique obtained as many as 30 people. Data collection techniques in this study were carried out by observing the value of respiratory rate before and after giving ACBT and effective cough. Data analysis using paired T-test.Results: the results showed a significant decrease in respiratory rate after the intervention (mean pre-test: 24.97, post-test: 22.97; p 0.001). These findings suggest that ACBT combined with effective coughing is an effective nursing intervention to manage respiratory symptoms in COPD patients.Conclusion: the conclusion is that there is an effect of the combination of Active Cycle of Breathing Technique (ACBT) and Effective Coughing on changes in repiratory rate in COPD patients.